The relationship between severe maternal morbidity and a risk of postpartum readmission among Korean women: a nationwide population-based cohort study - Jin Young Nam; Eun-Cheol Park (BMC, 2020)
Abstract Background As the rate of cesarean section delivery has increased, the incidence of severe maternal morbidity continues to increase. Severe maternal morbidity is associated with high medical costs, extended length of hospital stay, and long-term rehabilitation. However, there is no evidence whether severe maternal morbidity affects postpartum readmission. Therefore, this study aimed to determine the relationship between severe maternal morbidity and postpartum readmission. Methods This nationwide population-based cohort study used the Korean National Health Insurance Service-National Sample cohort of 90,035 delivery cases between January 2003 and November 2013. The outcome variable was postpartum readmission until 6 weeks after the first date of delivery in the hospital. Another variable of interest was the occurrence of severe maternal morbidity, which was determined using the Center for Disease Control and Prevention's algorithm. The Cox proportional hazard model was used to assess the association between postpartum readmission and severe maternal morbidity after all covariates were adjusted. Results The overall incidence of postpartum readmission was 2041 cases (0.95%) of delivery. Women with severe maternal morbidity had an approximately 2.4 times higher risk of postpartum readmission than those without severe maternal morbidity (hazard ratio 2.36, 95% confidence interval 1.75-3.19). In addition, compared with reference group, women who were aged 20-30 years, nulliparous, and delivered in a tertiary hospital were at high risk of postpartum readmission. Conclusions Severe maternal morbidity was related to the risk of postpartum readmission. Policy makers should provide a quality indicator of postpartum maternal health care and improve the quality of intrapartum care.